2018
DOI: 10.1088/1741-2552/aac810
|View full text |Cite
|
Sign up to set email alerts
|

Wireless opto-electro neural interface for experiments with small freely behaving animals

Abstract: The proposed WOENI device is potentially a versatile tool in the studies that involve long-term optogenetic neuromodulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Several researchers have also introduced variations of the Utaharray combined with miniaturized optical components to acquire high-resolution electrical neural signals following optical neurostimulation [127128]. Similarly, previous studies have reported the success of BMI systems based on optogenetic neuromodulation and electrical neural recordings in small animals [129130131132133134135]. For example, Liu et al developed a compact optogenetics system using graphene electrodes to reduce artifacts [136].…”
Section: Multi-modal Neural Probes To Measure Both Electrical and Optmentioning
confidence: 99%
“…Several researchers have also introduced variations of the Utaharray combined with miniaturized optical components to acquire high-resolution electrical neural signals following optical neurostimulation [127128]. Similarly, previous studies have reported the success of BMI systems based on optogenetic neuromodulation and electrical neural recordings in small animals [129130131132133134135]. For example, Liu et al developed a compact optogenetics system using graphene electrodes to reduce artifacts [136].…”
Section: Multi-modal Neural Probes To Measure Both Electrical and Optmentioning
confidence: 99%
“…[138] The second approach is implementing a wireless readout technology widely used for epidermal electronics. Wireless readout allows for a higher degree of freedom in animal experiments [129,139] as well as for humans. [140] Recently, even smaller than 1 mm size devices with CNT electrodes have been reported with such wireless communication abilities reducing further the motion induced damage to the brain tissue.…”
Section: Challenges In Signal Recording and Stimulationmentioning
confidence: 99%
“…More recently, Jia et al developed a battery‐powered flexible and implantable ECoG recording and optical stimulation device using commercially available μ‐ILEDs (220 × 270 × 50 μm 3 ). [ 231 ] A reflow soldering process mechanically holds μ‐ILEDs at desired locations and electrically connects the μ‐ILEDs to prepatterned interconnects. In vivo experiment demonstrates that the device can achieve the bidirectional neuromodulation of primary visual cortex neurons in freely moving rats using Bluetooth data communication for up to 21 days after implantation.…”
Section: Multimodal Microsystemsmentioning
confidence: 99%